AB0203 Expression levels of selected genes can predict the individual rheumatoid arthritis patient response to tumor necrosis factor alpha blocker treatment. (15th June 2017) - Paran, D; Smith, Y; Pundak, S; Arad, U; Levartovsky, D; Kaufman, I; Wollman, J; Furer, V; Broyde, A; Elalouf, O; Caspi, D; Pel, S; et al.
Abstract : Background: Rheumatoid arthritis (RA) patients have many therapeutic options. However, there are limited tools to predict the individual patient's response to therapy. The Genefron personal diagnostic kit (IFR 300) has been developed based on analysis of large databases to select interferon stimulated gene (ISG) expressions which could predict response to a biologic agent Objectives: This study aims to evaluate the ability of the Genefron diagnostic kit to predict the individual RA patient response to TNFα blockers. Methods: Two separate analyses were performed, one retrospective and one prospective analysis. The response of 61 RA patients reported in 2 published data sets was analyzed retrospectively utilizing the Genefron kit. In addition, 18 patients with RA were assessed prospectively, before and 3 months after starting treatment with a TNFα blocker. Clinical assessment included swollen and tender joint counts, patient and physician assessments of disease activity. Patients' blood samples were obtained before administration of the TNFα blocker and were analyzed utilizing the Genefron diagnostic kit which measures expression levels of selected genes by quantitative real time PCR. Results: Genefron kit analysis of retrospective data correctly predicted the response to a TNFα blocker in 53 of 61 RA patients (accuracy - 86.8%). In the prospective analysis 6 patients achieved a moderate EULAR response, 6 achieved a good EULAR response and 6 did not respond. According to the EULAR moderate response, the Genefron diagnostic kit predicted the response correctly in 16 of 18 patients (accuracy-89%, sensitivity -100%, specificity - 67%). According to the EULAR good response, the kit predicted the response correctly in 15 of 18 patients (accuracy - 83.3%, sensitivity - 100%, specificity - 75%). Conclusions: The Genefron diagnostic kit predicted the response to TNFα blockers in a high percentage of RA patients assessed either retrospectively or prospectively in a real life setting. This personal diagnostic kit has the ability to guide selection of a suitable biological drug for the individual RA patient Disclosure of Interest: None declared